BUDGETING AS A MECHANISM TO CONTROL THE COSTS OF AGRICULTURAL ENTERPRISES - Zotov V.P.; Konshina O.A.; Neustroeva E.V.; Chernichenko S.G. (Техника и технология пищевых производств, 2016)
The effectiveness of a company largely depends on the correct control strategies, the company economic potential, and the competitiveness of products including the level of costs. Today rational management involves a regulating directed increase on the "input - output" process. According to the authors, one of the mechanisms for the effective cost management is the mechanism of budgeting. The introduction of the budgeting system will increase the efficiency of the material and financial resources saving mode and enable the management to obtain objective information about the activities of the enterprise, to measure the performance of various functional areas and business units efficiently. The purpose of the research is to develop methodical bases of cost reduction in the manufacture of food products at AIC enterprises and to implement budgeting elements. To control the mechanism of cost management it is necessary to systematize the existing approaches in this problem highlighting the most important of them. Analysis of the economic literature on the problem has led to the conclusion that today there is no solid theoretical foundation for the "cost management" concept. In this regard, the authors formulate their own definition as follows: "Cost management is a system of influence on the constituent elements of procurement, production and sale processes of production, as well as the inputs and outputs of these processes through a dynamic information system of diagnostics of facilities’ costs, providing preventive and quick identification of potential areas for optimization and reduction of production costs and making effective management decisions in order to improve the competitiveness of enterprises". This definition allows us to identify a number of necessary conditions that form the basis of cost management: the systematic nature of management; the availability of relevant, actually-structured information for optimization of specific management costs; consideration of relationship between supply, production and marketing processes; focusing on improving the ability of enterprises to compete in a particular market.